Octopus Lipid and Vitamin E Composition: Interspecies, Interorigin, and Nutritional Variability - Alvaro Torrinha (2014)
Octopus vulgaris, Octopus maya, and Eledone cirrhosa from distinct marine environments [Northeast Atlantic (NEA), Northwest Atlantic (NWA), Eastern Central Atlantic, Western Central Atlantic (WCA), Pacific Ocean, and Mediterranean Sea] were characterized regarding their lipid and vitamin E composition. These species are those commercially more relevant worldwide. Significant interspecies and interorigin differences were observed. Unsaturated fatty acids account for more than 65% of total fatty acids, mostly omega-3 PUFA due to docosahexaenoic (18.4-29.3%) and eicosapentanoic acid (11.4-23.9%) contributions. The highest omega-3 PUFA amounts and omega-3/omega-6 ratios were quantified in the heaviest specimens, O. vulgaris from NWA, with high market price, and simultaneously in the lowest graded samples, E. cirrhosa from NEA, of reduced dimensions. Although having the highest cholesterol contents, E. cirrhosa from NEA and O. maya from WCA have also higher protective fatty acid indexes. Chemometric discrimination allowed clustering the selected species and several origins based on lipid and vitamin E profiles.